Surface Mechanism of Catalytic Electrodes in Lithium-Oxygen Batteries: How Nanostructures Mediate the Interfacial Reactions - Shen, Zhen-Zhen; Zhou, Chi; Wen, Rui; Wan, Li-Jun (Journal of the American Chemical Society, 2020)
The use of catalysts is the key to boost electrode reactions in lithium–oxygen (Li–O2) batteries. In-depth understanding of the nanoscale catalytic effect at electrode/electrolyte interfaces is of great significance for guiding a design of functionally optimized catalyst. Here, using electrochemical atomic force microscopy, we present the real-time imaging of interfacial evolution on nanostructured Au electrodes in a working battery, revealing that the nanostructure of Au is directly related to the catalytic activity toward oxygen reduction reaction (ORR)/oxygen evolution reaction (OER). In situ views show that nanoporous Au with a size of ∼14 nm for ligaments and ∼5 nm for nanopores promote the nucleation and growth of discharge product Li2O2 with large size at a high discharge voltage, yet densely packed Au nanoparticles with a diameter of ∼15 nm could catalyze Li2O2 to fully decompose via the top-bottom approach at a low charge potential. In addition, the difference in the nucleation potential of Li2O2 on the electrode with hybrid nanostructures could result in an uneven distribution of discharge products, which is alleviated at a large discharge rate and the capacity of the battery is improved significantly. These observations provide deep insights into the mechanisms of Li–O2 interfacial reaction catalyzed by nanostructured catalysts and strategies for improving Li–O2 batteries.